The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1073/pnas.240315897
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational modification of TEL and TEL/AML1 by SUMO-1 and cell-cycle-dependent assembly into nuclear bodies

Abstract: The E-26 transforming specific (ETS)-related gene, TEL, also known as ETV6, encodes a strong transcription repressor that is rearranged in several recurring chromosomal rearrangements associated with leukemia and congenital fibrosarcoma. TEL is a nuclear phosphoprotein that is widely expressed in all normal tissues. TEL contains a DNA-binding domain at the C terminus and a helixloop-helix domain (also called a pointed domain) at the N terminus. The pointed domain is necessary for homotypic dimerization and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 30 publications
4
87
0
Order By: Relevance
“…SUMO modification appears to play a role in a variety of cellular processes including protein-protein interaction, subcellular localization, protein stabilization and transcriptional regulation (Dohmen, 2004). A large number of SUMO target proteins have been identified, including several members of the Ets transcription factors family (Chakrabarti et al, 2000;Yang et al, 2003;Degerny et al, 2005;Leight et al, 2005;van den Akker et al, 2005;Wasylyk et al, 2005). Recently, we reported that the ERM Ets protein is sumoylated and that sumoylation of ERM represses its transcriptional activity (Degerny et al, 2005).…”
Section: Introductionmentioning
confidence: 89%
“…SUMO modification appears to play a role in a variety of cellular processes including protein-protein interaction, subcellular localization, protein stabilization and transcriptional regulation (Dohmen, 2004). A large number of SUMO target proteins have been identified, including several members of the Ets transcription factors family (Chakrabarti et al, 2000;Yang et al, 2003;Degerny et al, 2005;Leight et al, 2005;van den Akker et al, 2005;Wasylyk et al, 2005). Recently, we reported that the ERM Ets protein is sumoylated and that sumoylation of ERM represses its transcriptional activity (Degerny et al, 2005).…”
Section: Introductionmentioning
confidence: 89%
“…The SAM domain of PcG proteins mediates the interaction with UBC-9, leading to sumoylation, and directs the formation of subnuclear bodies whose characteristics are correlated with physiological function. Sumoylation itself has a variety of effects on its targets in cultured cells, including regulating the subnuclear localization of PML, HIPK2 and TEL [14][15][16] and modulating the transactivational activity of Sp3 and LEF1 (refs. 6,17).…”
Section: Sop-2(ph Sammentioning
confidence: 99%
“…Thus, intrinsic properties of the SAM domain may regulate the characteristics of nuclear body formation. The preferential sumoylation site in TEL, Lys99, is located within the SAM domain 14 , whereas the SAM domains of SOP-2 and PcG proteins lack the corresponding lysine residue and the sumoylated sites in SOP-2 seem to be outside the SAM domain (data not shown). To determine whether the distinct nuclear bodies formed in SOP-2(TEL SAM)::GFP were due to this sumoylation site, we mutated the TEL Lys99 to arginine within the chimeric construct.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…SUMO-1 modulates the interaction of the target protein with other cellular proteins and often results in changing the protein's location [9,27,43]. For example, a SUMO-attached protein may be transported to the nucleus [27,39].…”
Section: Upregulation Of Ubiquitin and Sumo Gene Families In The Pfc mentioning
confidence: 99%